ANALISIS RASIO PROFITABILITAS SEBAGAI ALAT UNTUK MENGUKUR KINERJA KEUANGAN PADA PT.BIRINGKASSI RAYA SEMEN TONASA GROUPJL. POROS TONASA 2 BONTOA MINASATE’NE PANGKEP - ika fatmawati; Moh Aris Pasigai; Faidhul Adzim (Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the profitability ratio to assess financial performance at PT. Biringkassi Raya Semen Tonasa Group. This type of research used in the research is descriptive quantitative. The focus of this study includes how profitability ratios as a tool to measure financial performance at PT. Biringkassi Raya in the last three years. This study was conducted to determine the profitability ratio analysis as a tool to measure the financial performance of PT. Biringkassi Raya in the last three years of the financial statements. The profitability ratio used is Net Profit Margin (NPM), Return On Equity (ROE) and Return On Assets (ROA). The results of the analysis show that financial performance is still not good, because the industry standard is still below standard. For Net Profit Margin, Return On Asset, and Return On Equtiy the company's financial performance is not good because the value achieved by the profitability ratio is still below the industry standard average.